Jawabanmu

2013-12-14T00:17:46+07:00
F(x) =  \frac{1-4x}{2x} + 3
g(x) = 4x - 6

a.(fog)(x) =    \frac{1 - 4(4x - 6)}{2(4x - 6)} + 3
(fog)(x) =    \frac{-16x + 25}{8x - 12} + 3

b. (gof)(x) = 4( \frac{1-4x}{2x} + 3) - 6
(gof)(x) =  \frac{4-16x}{2x} - 3
(gof)(x) =  \frac{4}{2x} + \frac{-16x}{2x} - 3
(gof)(x) =  \frac{2}{x} - 11
(gof)( \frac{1}{2x} ) = ( \frac{2}{\frac{1}{2x}}) - 11
(gof)( \frac{1}{2x} ) = 4x - 11

c. (fog)(x) =  \frac{-16x + 25}{8x - 12} + 3
(fog)(-3x) =  \frac{-16(-3x) + 25}{8(-3x) - 12} + 3
(fog)(-3x) =  \frac{48x + 25}{-24x - 12} + 3

d.(gof)(x) =  \frac{2}{x} - 11
(gof)(-1) =  \frac{2}{-1} - 11
(gof)(-1) = -2 - 11
(gof)(-1) = -13

Semoga Dapat Membantu